Superior excursion of the humeral head: A diagnostic tool in rotator cuff tear surgery - EROL, BÜLENT (MOSBY-ELSEVIER, 2005)
Superior excursion of the humeral head on the face of the glenoid was investigated to determine whether a relationship exists between the degree of humeral head excursion and the identify of the injured tendon in a shoulder with a torn rotator cuff. Twenty-seven patients with unilateral full-thickness rotator cuff tears diagnosed by either positive arthrogram or magnetic resonance imaging were included in this study. Three groups were formed based on intraoperative findings: 10 patients had isolated supraspinatus tendon tears (group 1), 11 patients had supraspinatus and infraspinatus tears (group 2), and 6 patients had supraspinatus, infraspinatus, and subscopularis tendon tears (group 3). There was no statistically significant difference between the degree of humeral head excursion in groups 1 and 2. However, patients in group 3 had a statistically significantly higher degree of excursion of the humeral head (P < .05) when compared with groups 1 and 2. In addition, an inverse relationship between the degree of humeral head excursion and preoperative Constant scores was found. Superior excursion of the humeral head on the glenoid had a significantly higher incidence in patients with subscopularis tears, and a larger amount of excursion was present in patients who had lower preoperative Constant scores.
Keywords: SUBSCAPULARIS TENDON; ISOLATED RUPTURE; SHOULDER; MUSCLE; JOINT